Positive electrode active material and fluoride ion battery
Copper halides as positive electrode active materials in fluoride ion batteries increase charge/discharge potential, enhancing energy density by stabilizing monovalent copper ions, thereby improving battery voltage.
Patent Information
- Application Number
- JP2022045056
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-03-22
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2042-03-22
AI Technical Summary
Existing fluoride ion batteries have limited battery voltage, necessitating an improvement in charge/discharge potential to enhance energy density.
Employing copper halides, specifically CuX (where X is Cl, Br, or I), as the positive electrode active material in fluoride ion batteries, which contain monovalent copper ions, allowing for increased charging and discharging potential.
The use of copper halides as positive electrode active materials results in fluoride ion batteries with higher battery voltage and improved energy density.
Smart Images

Figure 0007613401000001 
Figure 0007613401000002 
Figure 0007613401000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to positive electrode active materials and fluoride ion batteries. [Background technology]
[0002] Li-ion batteries, for example, are known as high-voltage and high-energy density batteries. Li-ion batteries are cation-based batteries that use Li ions as carriers. For example, Patent Document 1 discloses that metal fluorides or metal chlorides are used as the positive electrodes for lithium-ion batteries.
[0003] On the other hand, as an anion-based battery, a fluoride ion battery using fluoride ions as a carrier is known. Non-Patent Document 1 discloses a fluoride ion battery using BiF3, SnF2, CuF2 or KBiF4 as a positive electrode active material and Ce metal as a negative electrode active material, and discloses that the battery voltage is highest when CuF2 is used as a positive electrode active material and Ce metal is used as a negative electrode active material. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Special Publication No. 2020-507181 [Non-patent literature]
[0005] [Non-Patent Document 1] M. Anji et al., “Batteries based on fluoride shuttle”, J. Mater. Chem., 2011, 21, 17059 Summary of the Invention [Problem to be solved by the invention]
[0006] From the viewpoint of improving the energy density, it is desired to further improve the battery voltage of a fluoride ion battery. The present invention has been made in view of the above-mentioned circumstances, and has as its main object to provide a positive electrode active material having a high charge / discharge potential. [Means for solving the problem]
[0007] In order to solve the above problems, the present disclosure provides a positive electrode active material for use in a fluoride ion battery, the positive electrode active material being CuX (X is Cl, Br or I).
[0008] According to the present disclosure, the positive electrode active material used in the fluoride ion battery is a copper halide containing monovalent copper ions, thereby making it possible to increase the charge / discharge potential.
[0009] In the above disclosure, the positive electrode active material may contain at least CuCl.
[0010] In the above disclosure, the positive electrode active material may contain at least CuBr.
[0011] In the above disclosure, the positive electrode active material may contain at least CuI.
[0012] The present disclosure also provides a fluoride ion battery having a positive electrode active material layer, a negative electrode active material layer, and an electrolyte layer formed between the positive electrode active material layer and the negative electrode active material layer, wherein the positive electrode active material layer contains the above-mentioned positive electrode active material.
[0013] According to the present disclosure, by using the above-mentioned active material, a fluoride ion battery with a high battery voltage can be obtained. Effect of the Invention
[0014] The present disclosure has an effect of providing a positive electrode active material having a high charge / discharge potential. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of an all-solid-state battery according to the present disclosure. [Diagram 2] 4 is a graph showing the results of charge / discharge tests on the evaluation batteries of Examples 1 to 3 and a Comparative Example. [Diagram 3] 1 shows the results of XRD measurement of an evaluation battery in Example 1 before and after charging and discharging. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The positive electrode active material and the fluoride ion battery according to the present disclosure will be described in detail below.
[0017] A. Positive electrode active material The positive electrode active material in the present disclosure is a positive electrode active material for use in a fluoride ion battery, and is CuX (X is Cl, Br, or I).
[0018] According to the present disclosure, the positive electrode active material used in a fluoride ion battery is a copper halide containing monovalent copper ions, which allows the charge and discharge potential to be increased. Here, Non-Patent Document 1 describes that the discharge potential of a battery using CuF2 as the positive electrode active material and Ce metal as the negative electrode active material is about 2.7 V. In CuF2, zero-valent metallic copper (Cu) and divalent copper ions (Cu 2+ ) is used. In copper (divalent copper) fluoride, the monovalent copper ion (Cu + ) cannot exist stably.
[0019] On the other hand, CuX (X is Cl, Br, or I) in the present disclosure is a copper halide in which monovalent copper ions can exist stably. Therefore, the monovalent copper ions (Cu + ) and divalent copper ions (Cu 2+ ) the reaction potential shifts to a more noble potential, allowing it to have a higher charge / discharge potential than CuF2.
[0020] The positive electrode active material in the present disclosure may be any one of CuCl, CuBr, and CuI, or may be a mixture of two or more of them. The positive electrode active material preferably contains at least CuCl. In this case, the positive electrode active material may contain only CuCl, or may contain at least one of CuCl, CuBr, and CuI. In addition, the positive electrode active material preferably contains at least CuBr. In this case, the positive electrode active material may contain only CuBr, or may contain at least one of CuCl and CuI. In addition, the positive electrode active material preferably contains at least CuI. In this case, the positive electrode active material may contain only CuI, or may contain at least one of CuI, CuCl, and CuBr. In addition, the positive electrode active material in the present disclosure is usually fluorinated during charging of a fluoride ion battery and defluorinated during discharging.
[0021] The shape of the positive electrode active material in the present disclosure may be, for example, a particulate shape (positive electrode active material particles). Specific shapes of the positive electrode active material particles may be, for example, a true sphere, an oval sphere, etc. The average particle diameter (D 50 ) is preferably within the range of 10 nm to 50 μm, and more preferably within the range of 20 nm to 10 μm. The average particle size of the positive electrode active material particles can be measured, for example, by observation with a scanning electron microscope (SEM) (for example, n≧20). It can also be calculated from the measured value of the BET specific surface area.
[0022] B. Fluoride-ion battery Fig. 1 is a schematic cross-sectional view showing an example of a fluoride ion battery in the present disclosure. The fluoride ion battery 10 shown in Fig. 1 has a positive electrode active material layer 1, a negative electrode active material layer 2, an electrolyte layer 3 formed between the positive electrode active material layer 1 and the negative electrode active material layer 2, a positive electrode current collector 4 that collects current from the positive electrode active material layer 1, a negative electrode current collector 5 that collects current from the negative electrode active material layer 2, and a battery case 6 that houses these members. In the present disclosure, the positive electrode active material layer 1 is a fluoride ion battery having a positive electrode active material layer 1 and a negative electrode active material layer 2, and a positive electrode active material layer 3 and a negative electrode active material layer 4 and a negative electrode active material layer 5. The major feature of the present invention is that it contains the positive electrode active material described above.
[0023] According to the present disclosure, by using the above-mentioned positive electrode active material, a fluoride ion battery with a high battery voltage can be obtained.
[0024] 1.Cathode active material layer The positive electrode active material layer in the present disclosure is a layer containing at least the positive electrode active material described above. The positive electrode active material is the same as that described in "A. Positive electrode active material" above. The positive electrode active material layer may contain only the positive electrode active material described above, or may also contain other active materials. In the latter case, the ratio of the positive electrode active material described above in the entire active material is, for example, 85% by weight or more, may be 90% by weight or more, may be 95% by weight or more, or may be 99% by weight or more.
[0025] The content of the positive electrode active material in the positive electrode active material layer is, for example, 10% by weight or more and 90% by weight or less, or may be 20% by weight or more and 80% by weight or less, or may be 30% by weight or more and 70% by weight or less. If the proportion of the positive electrode active material is too small, the energy density may decrease.
[0026] Furthermore, the positive electrode active material layer may further contain at least one of a conductive material, a binder, and an electrolyte, if necessary.
[0027] The conductive material is not particularly limited as long as it has the desired electronic conductivity, and examples of the conductive material include carbon materials, such as carbon blacks such as acetylene black, ketjen black, furnace black, and thermal black, carbon fibers, fibrous carbon materials such as carbon nanotubes (CNTs) and carbon nanofibers (CNFs), graphene, graphite, and fullerenes.
[0028] The content of the conductive material in the positive electrode active material layer is, for example, 1% by weight or more, may be 5% by weight or more, or may be 10% by weight or more. On the other hand, the content of the conductive material is, for example, 20% by weight or less, may be 15% by weight or less. If the proportion of the conductive material is too small, a good electron conduction path may not be formed, and if the proportion of the conductive material is too large, the proportion of the active material may be relatively small, and the energy density may decrease.
[0029] There are no particular limitations on the binder as long as it is chemically and electrically stable, and examples of the binder include fluorine-based binders such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE).
[0030] The electrolyte is the same as that described in "3. Electrolyte Layer" below. The content of the electrolyte in the positive electrode active material layer is, for example, 5% by weight or more, and may be 10% by weight or more. On the other hand, the content of the electrolyte is, for example, 70% by weight or less, and may be 40% by weight or less. If the proportion of the electrolyte is too small, it may not be possible to diffuse fluoride ions to the depth of the positive electrode active material layer with low resistance. If the proportion of the electrolyte is too high, the proportion of the active material will be relatively small, and the energy density may decrease.
[0031] The thickness of the positive electrode active material layer is, for example, 0.1 μm or more and 1000 μm or less.
[0032] 2.Negative electrode active material layer The negative electrode active material layer in the present disclosure is a layer containing at least a negative electrode active material. The negative electrode active material layer may further contain at least one of a conductive material, an electrolyte, and a binder, as necessary.
[0033] As the negative electrode active material, any active material having a lower potential than the positive electrode active material can be selected. As the negative electrode active material, for example, a fluoride of a metal element, a fluoride of an alloy, or a fluoride of a metal oxide can be mentioned. As the metal element contained in the negative electrode active material, for example, La, Ca, Al, Eu, Li, Si, Ge, Sn, In, V, Cd, Cr, Fe, Zn, Ga, Ti, Nb, Mn, Yb, Zr, Sm, Ce, Mg, Pb, etc. can be mentioned. Among them, the negative electrode active material is preferably MgFx, AlFx, LaFx, CeFx, CaFx, or PbFx. Note that the above x is a real number greater than 0.
[0034] The conductive material and binder may be the same as those described in "1. Positive electrode active material layer" above. The electrolyte is the same as that described in "3. Electrolyte layer", so the description here is omitted.
[0035] The content of the negative electrode active material in the negative electrode active material layer is preferably as high as possible from the viewpoint of capacity, for example, 30% by weight or more, preferably 50% by weight or more, and more preferably 70% by weight or more. The thickness of the negative electrode active material layer is, for example, 0.1 μm or more and 1000 μm or less.
[0036] 3. Electrolyte layer The electrolyte layer in the present disclosure is a layer formed between a positive electrode active material layer and a negative electrode active material layer. The electrolyte constituting the electrolyte layer may be a liquid electrolyte (electrolytic solution), a polymer electrolyte, or an inorganic solid electrolyte.
[0037] The electrolyte contains, for example, a fluoride salt and a solvent. Examples of the fluoride salt include inorganic fluoride salts, organic fluoride salts, and ionic liquids. Examples of the inorganic fluoride salt include XF (X is Li, Na, K, Rb, or Cs). Examples of the cation of the organic fluoride salt include alkyl ammonium cations such as tetramethylammonium cations. The concentration of the fluoride salt in the electrolyte is, for example, 0.1 mol / L or more, may be 0.3 mol / L or more, or may be 0.5 mol / L or more. On the other hand, the concentration of the fluoride salt is, for example, 6 mol / L or less, and may be 3 mol / L or less.
[0038] The solvent may be, for example, R 1 -O(CH2CH2O) n -R 2 (R 1 and R 2 are each independently an alkyl group having 4 or less carbon atoms or a fluoroalkyl group having 4 or less carbon atoms, and n is within a range of 2 to 10), cyclic carbonates such as ethylene carbonate (EC), fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), propylene carbonate (PC), and butylene carbonate (BC), and chain carbonates such as dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). The electrolytic solution may contain an alkali metal amide salt. The polymer electrolyte can be obtained, for example, by adding a polymer to a liquid electrolyte and gelling it.
[0039] On the other hand, examples of inorganic solid electrolytes include fluorides having lanthanoid elements such as La and Ce, fluorides having alkali metal elements such as Li, Na, K, Rb, and Cs, and fluorides having alkaline earth elements such as Ca, Sr, and Ba. In addition, the inorganic solid electrolyte is preferably a fluoride having at least one metal element selected from La, Ba, Pb, Sn, Ca, and Ce. The inorganic solid electrolyte may have only one of the above metal elements, or may have two or more of them. Specific examples of inorganic solid electrolytes include La,1-x Ba x F 3-x (0≦x≦1), Pb 2-x Sn x F4(0≦x≦2), Ca 2-x Ba x F4(0≦x≦2) and Ce 1-x Ba x F 3-x (0≦x≦1). Each of the x's may be greater than 0, 0.3 or greater, 0.5 or greater, or 0.9 or greater. Each of the x's may be smaller than 1, 0.9 or less, 0.5 or less, or 0.3 or less. The shape of the inorganic solid electrolyte is not particularly limited, but may be, for example, particulate.
[0040] 4.Other configurations The fluoride ion battery in the present disclosure has at least the above-mentioned positive electrode active material layer, negative electrode active material layer, and electrolyte layer. In addition, it usually has a positive electrode current collector that collects the current of the positive electrode active material layer, a negative electrode current collector that collects the current of the negative electrode active material layer, and a battery case that houses the above-mentioned members. The materials of the positive electrode current collector, the negative electrode current collector, and the battery case can be conventionally known materials. The shape of the current collector can be, for example, a foil shape, a mesh shape, or a porous shape. The fluoride ion battery may also have a separator between the positive electrode active material layer and the negative electrode active material layer. By providing a separator, a safer battery can be obtained.
[0041] 5. Fluoride-ion batteries The fluoride ion battery in the present disclosure may be a liquid battery or an all-solid-state battery, but is preferably an all-solid-state battery. The fluoride ion battery in the present disclosure may be a primary battery or a secondary battery, but is preferably a secondary battery. This is because the battery can be repeatedly charged and discharged, and is useful, for example, as an in-vehicle battery. The shape of the fluoride ion battery in the present disclosure may be, for example, a coin type, a laminate type, a cylindrical type, or a square type.
[0042] The present disclosure is not limited to the above-described embodiment. The above-described embodiment is merely an example, and any configuration that is substantially the same as the technical idea described in the claims of the present disclosure and that exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES
[0043] [Example 1] (Preparation of evaluation battery) CuCl (Aldrich) and solid electrolyte La 0.9 Ba 0.1 F 2.9 The positive electrode mixture was obtained by mixing the LaF3 and BaF2 (both manufactured by Kojundo Chemical Co., Ltd.) in a ball mill and then firing them at 600°C with a conductive material in a weight ratio of 30:60:10 in a ball mill (rotation speed 100 rpm). The obtained mixture (working electrode) and the solid electrolyte (La 0.9 Ba 0.1 F 2.9 A counter electrode made of a mixture of PbF2 (manufactured by Kojundo Chemical) and acetylene black HS-100 (manufactured by Denka) in a weight ratio of 95:5 was pressed together with Pb foil to obtain a battery for evaluation.
[0044] (Charge / discharge evaluation) A charge / discharge test was carried out on the evaluation battery obtained in Example 1. The charge / discharge test was carried out at a temperature of 140° C., a cut-off potential of 1.5 (vs. Pb / PbF2) to 0.3 V (vs. Pb / PbF2), and 50 μA. The results are shown in FIG. 2(a). The average discharge potential was 0.90 V (vs. Pb / PbF2).
[0045] (XRD measurement) X-ray diffraction (XRD) measurements using CuKa radiation were performed on the working electrode of the evaluation battery obtained in Example 1 before and after charging and discharging using an Ultima IV (manufactured by Rigaku). The measurement conditions were an Ar atmosphere, 2θ=10 to 80°, a scanning speed of 2° / min, and a measurement interval of 0.02°. The results are shown in FIG. 3.
[0046] Before charging and discharging, the peak of the active material CuCl and the peak of the electrolyte La0.9 Ba 0.1 F 2.9 A peak at 2θ=15° can be confirmed. When the positive electrode active material is fluorinated by charging, a peak appears at 2θ=15° that can be assigned to a structure similar to CuCl2 (after charging to 1.5 V). It is assumed that CuClF is generated when CuCl is fluorinated by charging, but this material has not been reported in the database. Presumably, CuClF and CuCl2 have the same crystal structure, and the peak at 2θ=15° is thought to be derived from CuClF. It was also confirmed that after discharging, it is defluorinated and reversibly returns to the CuCl structure (after charging to 1.5 V and discharging to 0.3 V). Therefore, it is assumed that the charge / discharge reaction of CuCl is a reaction between CuCl (monovalent copper ion) and CuClF (divalent copper ion).
[0047] [Example 2] Except for changing the positive electrode active material of Example 1 to CuBr (manufactured by Aldrich), an evaluation battery was prepared in the same manner as in Example 1, and charge / discharge evaluation was performed. The results are shown in Figure 2(b). The average discharge potential was 0.48 V (vs. Pb / PbF2).
[0048] [Example 3] Except for changing the positive electrode active material of Example 1 to CuI (manufactured by Aldrich), an evaluation battery was prepared in the same manner as in Example 1, and charge / discharge evaluation was performed. The results are shown in Figure 2(c). The average discharge potential was 0.57 V (vs. Pb / PbF2).
[0049] [Comparative Example] Except for changing the positive electrode active material of Example 1 to CuF2 (manufactured by Strem Chemicals), an evaluation battery was prepared in the same manner as in Example 1, and charge / discharge evaluation was performed. The results are shown in Figure 2(d). The average discharge potential was 0.33 V (vs. Pb / PbF2).
[0050] From the results of FIGS. 2(a) to (d), it was confirmed that the evaluation batteries of Examples 1 to 3 had a higher initial discharge potential than the evaluation battery of the Comparative Example. It was also confirmed that the evaluation batteries of Examples 1 to 3 had a higher charge potential than the evaluation battery of the Comparative Example. That is, it was confirmed that the positive electrode active materials (CuCl, CuBr, and CuI) used in Examples 1 to 3 had a higher charge / discharge potential than the positive electrode active material (CuF2) used in the Comparative Example. The positive electrode active materials used in Examples 1 to 3 were copper halides in which monovalent copper ions can exist stably, and therefore monovalent copper ions (Cu + ) and divalent copper ions (Cu 2+ It is presumed that the reaction potential shifted to a more noble potential due to oxidation-reduction between the two. [Explanation of symbols]
[0051] 1...Cathode active material layer 2...Negative electrode active material layer 3...electrolyte layer 4...Positive electrode current collector 5...Negative electrode current collector 6. Battery case 10...Fluoride-ion battery
Claims
1. A positive electrode active material for use in a fluoride ion battery, comprising: The positive electrode active material is a copper halide containing a monovalent copper ion, The copper halide is CuX (X is Br or I).
2. The positive electrode active material according to claim 1 , wherein the positive electrode active material contains at least CuBr.
3. The positive electrode active material according to claim 1 or 2, wherein the positive electrode active material contains at least CuI.
4. A fluoride ion battery having a positive electrode active material layer, a negative electrode active material layer, and an electrolyte layer formed between the positive electrode active material layer and the negative electrode active material layer, A fluoride ion battery, wherein the positive electrode active material layer contains the positive electrode active material according to any one of claims 1 to 3.
Citation Information
Patent Citations
Halogen secondary battery
JP2015176704A
Halogen secondary battery
JP2016051646A
Graphene foam-protected metal fluoride and metal chloride cathode active materials in lithium batteries
JP2020507181A
Catalytic solution for halide ion battery
WO2022186394A1